Hands-On Mobile and Embedded Development with Qt 5 : Build apps for Android, iOS, and Raspberry Pi with C++ and Qt /: Build apps for Android, iOS, and Raspberry Pi with C++ and Qt. (2019) - Potter, Lorn
No abstract available